2021
DOI: 10.14639/0392-100x-n1146
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear implant in prelingually hearing-impaired adults: prognostic factors and results

Abstract: Objectives. The aim of present study is to evaluate the impact of prognostic factors on the outcome in a group of prelingually hearing-impaired patients submitted to cochlear implantation (CI) at an adult age. Methods. This is a retrospective study on a cohort of prelingually severe-to-profound hearing-impaired patients cochlear implanted in adulthood and followed by a single audiology centre. We correlated post-CI results in term of speech perception with patients' speech perception with hearing aids before i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Amongst pre-lingually deaf patients implanted as adolescents or adults, few achieved open-set speech perception [ 16 , 18 , 22 , 26 , 29 , 33 , 35 ], consistent with outcomes reported from non-syndromic populations [ 42 ]. Auditory outcomes appear similar to those of pre-lingually deaf patients with normal vision [ 3 , 29 , 30 , 42 ]. Henricson et al [ 40 ] found that auditory information processing performance in children with Usher type 1 was similar to that of children with normal hearing, except in tests of phonological working memory and lexical skill.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Amongst pre-lingually deaf patients implanted as adolescents or adults, few achieved open-set speech perception [ 16 , 18 , 22 , 26 , 29 , 33 , 35 ], consistent with outcomes reported from non-syndromic populations [ 42 ]. Auditory outcomes appear similar to those of pre-lingually deaf patients with normal vision [ 3 , 29 , 30 , 42 ]. Henricson et al [ 40 ] found that auditory information processing performance in children with Usher type 1 was similar to that of children with normal hearing, except in tests of phonological working memory and lexical skill.…”
Section: Discussionmentioning
confidence: 64%
“…Much of this may be accounted for by the effect of patient age at implantation. Several studies of non-syndromic pediatric patients have identified a transition period between the ages of 24–36 months after which implantation results in relatively inferior perceptive and communicative outcomes [ 3 ]. Amongst studies of Usher syndrome, Loundon et al [ 29 ] reported better perceptive results in children implanted below the age of nine years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But we need to get to the last decades of the last century to have, on the one hand, the diffusion of "universal newborn hearing screening", the discovery of the genetic causes of over half of congenital deafness, and on the other hand, the cochlear implants that have allowed thousands of children born deaf the development of normal speech [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, age can also be related to other factors, such as cognition and duration of hearing loss. Previous studies have examined such patient-dependent factors impacting outcomes including education level, patient gender, etiology of hearing loss, duration of hearing loss, and cognitive function (6)(7)(8). However, these studies have found the associations to be weak, and they do not explain the wide range of variability among patient outcomes.…”
Section: Introductionmentioning
confidence: 99%